Changes in Hospital Inpatient Utilization Following Health Care Reform. (30th June 2017) - Pickens, Gary; Karaca, Zeynal; Cutler, Eli; Dworsky, Michael; Eibner, Christine; Moore, Brian; Gibson, Teresa; Iyer, Sharat; Wong, Herbert S.
Abstract : Objective: To estimate the effects of 2014 Medicaid expansions on inpatient outcomes. Data Sources: Health Care Cost and Utilization Project State Inpatient Databases, 2011–2014; population and unemployment estimates. Study Design: Retrospective study estimating effects of Medicaid expansions using difference‐in‐differences regression. Outcomes included total admissions, referral‐sensitive surgical and preventable admissions, length of stay, cost, and patient illness severity. Findings: In 2014 quarter four, compared with nonexpansion states, Medicaid admissions increased (28.5 percent, p = .006), and uninsured and private admissions decreased (–55.1 percent, p = .001, and –6.6 percent, p = .052), whereas all‐payer admissions showed little change. Uninsured expansion effects were negative for preventable admissions (−24.4 percent, p = .068), length of stay (–9.3 percent, p = .039), total cost (−9.2 percent, p = .128), and illness severity (−4.5 percent, p = .397). Significant positive expansion effects were found for Medicaid referral‐sensitive surgeries (11.8 percent, p = .021) and patient illness severity (2.3 percent, p = .015). Private and all‐payer expansion effects for outcomes other than admission volume were small and mainly nonsignificant ( p > .05). Conclusion: Medicaid expansions did not change all‐payer admission volumes, but they were associated with increased Medicaid and decreased uninsured volumes. Results suggest those previously uninsured with greater needs for inpatient services were most likely to gain coverage. Compositional changes in uninsured and Medicaid admissions may be due to selection.